Real Time Central Assessment of Kidney Transplant Indication Biopsies by Microarrays: The INTERCOMEX Study. Issue 11 (30th May 2017) - Halloran, P. F.; Reeve, J.; Akalin, E.; Aubert, O.; Bohmig, G. A.; Brennan, D.; Bromberg, J.; Einecke, G.; Eskandary, F.; Gosset, C.; Duong Van Huyen, J.‐P.; Gupta, G.; et al.
Abstract : The authors conducted a prospective trial to assess the feasibility of real time central molecular assessment of kidney transplant biopsy samples from 10 North American or European centers. Biopsy samples taken 1 day to 34 years posttransplantation were stabilized in RNA later, sent via courier overnight at ambient temperature to the central laboratory, and processed (29 h workflow) using microarrays to assess T cell– and antibody‐mediated rejection (TCMR and ABMR, respectively). Of 538 biopsy samples submitted, 519 (96%) were sufficient for microarray analysis (average length, 3 mm). Automated reports were generated without knowledge of histology and HLA antibody, with diagnoses assigned based on Molecular Microscope Diagnostic System (MMDx) classifier algorithms and signed out by one observer. Agreement between MMDx and histology (balanced accuracy) was 77% for TCMR, 77% for ABMR, and 76% for no rejection. A classification tree derived to provide automated sign‐outs predicted the observer sign‐outs with >90% accuracy. In 451 biopsy samples where feedback was obtained, clinicians indicated that MMDx more frequently agreed with clinical judgment (87%) than did histology (80%) (p = 0.0042). In 81% of feedback forms, clinicians reported that MMDx increased confidence in management compared with conventional assessment alone. The authors conclude that real time central molecular assessment is feasible and offers a useful new dimension in biopsy interpretation. ClinicalTrials.gov NCT#01299168. Abstract : An international trial to study the feasibility and effectiveness of real‐time central microarray processing of kidney transplant biopsies, interpreted by the Molecular Microscope Diagnostic System, finds that 96% of all biopsies received could be reported, and participating clinicians indicate considerable potential of this method to change care.